Vertrek vanaf de Javakade van de Groote Beer. Leuze op kap C.S.. Twee aan elkaar te leggen foto's - Kruger, Dolf,
Vertrek vanaf de Javakade van de Groote Beer. Leuze op kap C.S.. Twee aan elkaar te leggen foto's.